If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6 = 20x + 2 Reorder the terms: -6 + 4x = 20x + 2 Reorder the terms: -6 + 4x = 2 + 20x Solving -6 + 4x = 2 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -6 + 4x + -20x = 2 + 20x + -20x Combine like terms: 4x + -20x = -16x -6 + -16x = 2 + 20x + -20x Combine like terms: 20x + -20x = 0 -6 + -16x = 2 + 0 -6 + -16x = 2 Add '6' to each side of the equation. -6 + 6 + -16x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -16x = 2 + 6 -16x = 2 + 6 Combine like terms: 2 + 6 = 8 -16x = 8 Divide each side by '-16'. x = -0.5 Simplifying x = -0.5
| .6(4.8+.9x+.7x)=2.4 | | 7y^3-20y^2-3=0 | | 15t-7-(-8)-9t-(-6t)= | | 8u-5=0 | | ln(x-1)+ln(6)=ln(3x) | | 5.2-.7-.4x+.7x=5.4 | | 6+9*x+8*x= | | 3x-2=3x+4 | | (x+3)(x-2-5i)(x-2+5i)=0 | | 4=x-7.2 | | (x-3)(x-2-5i)(x-2+5i)=0 | | 726=33*x | | 704=32*x | | 3x^2-49x-130= | | -3(22-8)+102=16 | | 825=2500(0.055)t | | 17y=306 | | 42=18+14(t+5) | | 47y=517 | | 108=4.325(b+12.50) | | (9-u)(4+4u)= | | 3.4+.3-x-2x=4.3 | | r(24)=-3 | | 11x+6=6x-9 | | 32y=5344 | | (2x+6)+(9x-5)= | | -8=c(12) | | 5-4y=3 | | 20=q(-5) | | -4y+5x=3 | | 6=5/6(12-b)+1 | | 15+3(3u-1)=16-(3u-8) |